Gastro‐oesophageal reflux disease in 20 dogs (2012 to 2014). (24th February 2017) - Muenster, M.; Hoerauf, A.; Vieth, M.
Abstract : Objectives: To describe the clinical features of canine gastro‐oesophageal reflux disease. Materials and Methods: A search of our medical records produced 20 dogs with clinical signs attributable to oesophageal disease, hyper‐regeneratory oesophagopathy and no other oesophageal disorders. The clinical, endoscopic and histological findings of the dogs were analysed. Results: The 3‐year incidence of gastro‐oesophageal reflux disease was 0·9% of our referral dog population. Main clinical signs were regurgitation, discomfort or pain (each, 20/20 dogs) and ptyalism (18/20 dogs). Oesophagoscopy showed no (5/20 dogs) or minimal (13/20 dogs) mucosal lesions. In oesophageal mucosal biopsy specimens, there were hyperplastic changes of the basal cell layer (13/20 dogs), stromal papillae (14/20 dogs) and entire epithelium (9/20 dogs). Eleven dogs received omeprazole or pantoprazole and regurgitation and ptyalism improved in eight and pain diminished in six of these dogs within three to six weeks. Clinical Significance: Our findings suggest that canine gastro‐oesophageal reflux disease is a more common clinical problem than hitherto suspected.